Evaluating biological agents and plant extracts against Aspergillus niger in pomegranate fruit rot and Ochratoxin A prevention - Fatima Haider Abd-zaid Al-fatlawi; Yasir Naser Alhamiri (Journal of Kerbala for Agricultural Sciences, 2024)
The aim of the research was to conduct an ecological and biological survey of the extent of pomegranate fruit rot disease and to identify the fungi responsible for these cases in Iraq. The study involved isolating and identifying pathogenic Aspergillus niger isolates capable of producing the mycotoxin Ochratoxin A and evaluating the effects of certain plant extracts, agricultural fungicides, and the yeast S. cerevisiae in protecting pomegranate fruits from A. niger attack during storage. The isolation and identification results revealed that all samples were contaminated with various fungal isolates, with a contamination rate of 100%. The storage experiment results showed that percentage of disease severity, coriander extract significantly reduced the severity to 8.53%, compared to 23.23% for the pathogen-only treatment, with a fungal inhibition rate of 63.28%. This was followed by the treatment with sage extract, which reduced the severity to 10.13% with an inhibition rate of 56.39%. Lastly, the plant-based pesticide Palizin and the biological agent (S. cerevisiae) achieved reductions in disease severity of 11.86% and 10.73%, respectively, with inhibition rates of 45.94% and 53.80% compared to the control treatment. The results showed that treating stored pomegranate fruits with alcoholic coriander extract reduction in the levels of Ochratoxin A, production, with a reduction percentage of 6.92%. The A. niger fungal isolate was able to resist the effect of the plant extract and produce the mycotoxin Ochratoxin A, at a rate of 57.8 microgram/kg, compared to the pathogen-only treatment, which resulted in toxin production of 62.1 microgram/kg.